2004
DOI: 10.2337/diacare.27.7.1565
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Excretion Rate Is Not Affected by Asymptomatic Urinary Tract Infection

Abstract: OBJECTIVE—The aim of the study was to evaluate whether asymptomatic urinary tract infection (UTI) significantly influences the level of albumin excretion rate (AER) in diabetic patients. RESEARCH DESIGN AND METHODS—We screened prospectively for UTI and AER in 765 type 2 diabetic subjects. AER was determined before and after antimicrobial therapy in those patients in whom an asymptomatic UTI was diagnosed (n = 59). To interpret the clinical significance of AER changes, the coefficient of biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Considering the importance of microalbuminuria screening for diabetes care, this observation is even more relevant. In fact, we had previously demonstrated that the treatment of bacteriuria did not significantly change urinary albumin values in patients with diabetes [6], as also suggested by others [7]. …”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…Considering the importance of microalbuminuria screening for diabetes care, this observation is even more relevant. In fact, we had previously demonstrated that the treatment of bacteriuria did not significantly change urinary albumin values in patients with diabetes [6], as also suggested by others [7]. …”
Section: Resultsmentioning
confidence: 54%
“…However, the small number of studies with the same albuminuria techniques precludes an adequate evaluation. Another potential issue to take into account is that when the study by Hernandez and Simo [7] was excluded from analysis, the lack of the association of micro- and macroalbuminuria was gone and a lower heterogeneity was found. Nevertheless, we should acknowledge that no peculiarity (characteristics of the patients, measurements methods, blood pressure levels, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations